2009
DOI: 10.1016/j.jhep.2009.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment with pegylated interferon plus ribavirin of chronic hepatitis C non-responders to interferon plus ribavirin: A meta-analysis

Abstract: Background/Aims: Efficacy of retreatment with pegylated interferon (PEG-IFN) plus ribavirin of non-responders to standard or pegylated IFN plus ribavirin has been assessed in various studies, but sustained virologic response (SVR) rates are variable and factors influencing efficacy and tolerability still remain incompletely defined. We aimed to focus on SVR rates and to identify factors influencing them in this meta-analysis.Methods: MEDLINE as well as a manual search were used. Studies were included if they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…While a systematic review for all arms receiving A/R was not conducted, the A/R arms used in the present study were selected based on objective criteria (use as a comparator arm to another studied regimen) and reflect the performance of A/R in trials with similar designs to the included DCV + ASV trials. In addition, SVR rates among the A/R arms used in this study are consistent with those reported in the literature in both treatment-naive and treatmentexperienced patients [7,[51][52][53][54][55]. Other novel IFN-free combination regimens (e.g., ledipasvir-SOF, ombitasvir-paritaprevir-ritonavir + dasabuvir and SOF-SMV) have been recently approved for treatment of HCV infection with rates of SVR exceeding 90% [56][57][58][59].…”
Section: Discussionsupporting
confidence: 81%
“…While a systematic review for all arms receiving A/R was not conducted, the A/R arms used in the present study were selected based on objective criteria (use as a comparator arm to another studied regimen) and reflect the performance of A/R in trials with similar designs to the included DCV + ASV trials. In addition, SVR rates among the A/R arms used in this study are consistent with those reported in the literature in both treatment-naive and treatmentexperienced patients [7,[51][52][53][54][55]. Other novel IFN-free combination regimens (e.g., ledipasvir-SOF, ombitasvir-paritaprevir-ritonavir + dasabuvir and SOF-SMV) have been recently approved for treatment of HCV infection with rates of SVR exceeding 90% [56][57][58][59].…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies showed heterogeneous SVR rates and they also showed differences in design and power of the studies, potential biases in the selection of patients with different demographic, clinical and virologic characteristics, the variability in the doses of IFN and ribavirin, and the different treatment stopping rule of the first course of therapy. Camma et al31 conducted meta-analysis of 14 trials on retreatment with PEG-IFN and ribavirin in chronic hepatitis C patients who failed to respond to IFN or PEG-IFN and ribavirin. This meta-analysis of data from 14 studies, comprising nearly 4,000 nonresponders to combination therapy, reported that retreatment with a course of 48 weeks of PEG-IFN and ribavirin achieved a SVR in 16% of patients with a 12% withdrawal rate due to adverse reactions or intolerance to drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype 1 HCV infection accounts for about 75% of all cases in the US and is the most difficult to treat of the six identified genotypes [8], [9]. Among treatment-naïve patients with genotype 1 HCV infection, therapy with a 48-week course of peginterferon and ribavirin (PR) historically has yielded clinical trial SVR rates ranging from 42% to 46% [10], [11]; re-treatment with PR has been associated with lower SVR rates (16.3%) [12].…”
Section: Introductionmentioning
confidence: 99%